Vake (Value and Knowledge) Approach to Enhance The Role of Professional Teachers and Achieving SDGS 4 at SIKK, Malaysia - Mardiani, Desika Putri; Rosyanafi, Rofik Jalal; Nusantara, Widya; Qodriyati, Tri 'Ulya; Susanto , Shobri Firman; Mustakim, Mustakim; Widyaswari, Monica (Jurnal Pengabdian UNDIKMA, 2025)
This community service program aims to enhance the professional competence of SIKK teachers through VAKE-based training that integrates moral and knowledge dimensions in the teaching process. The training was attended by 32 teachers and implemented through collaborative learning. Pre-test, post-test, and ethical dilemma creation were used as analysis techniques. These data were analyzed descriptively to calculate mean scores, percentage increases, and N-gain values to determine improvements in participants’ understanding of the VAKE approach. The results showed an increase in teachers’ understanding of the integration of values and knowledge in learning, with an average score of 88.6, indicating an improvement of 8.6 points (43.5%) compared to the pre-test results. This finding suggests that participants’ understanding improved significantly after receiving the training materials through the community service program. Participants also successfully designed ethical dilemmas as learning media to promote students’ critical thinking. Overall, this community service program contributed to improving teachers’ pedagogical competence, strengthening students’ character, and supporting the achievement of Sustainable Development Goal (SDG) 4.